2023
DOI: 10.3389/fmolb.2022.1106588
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 core domain in chromatin with different DNA linker lengths studied by 1H-Detected solid-state NMR spectroscopy

Abstract: Chromatin, a dynamic protein-DNA complex that regulates eukaryotic genome accessibility and essential functions, is composed of nucleosomes connected by linker DNA with each nucleosome consisting of DNA wrapped around an octamer of histones H2A, H2B, H3 and H4. Magic angle spinning solid-state nuclear magnetic resonance (NMR) spectroscopy can yield unique insights into histone structure and dynamics in condensed nucleosomes and nucleosome arrays representative of chromatin at physiological concentrations. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Since phase separation conditions can affect the quality of the solution NMR spectra, we used substoichiometric ratios of pHP1α to mononucleosomes, which resulted in clear samples without droplets (Figure S5) and yielded well resolved assignable spectra (Figure b). We also note that we performed all NMR structural studies (both solution and solid state) under low salt conditions to compare to previous work and to take advantage of published assignments. …”
Section: Resultsmentioning
confidence: 99%
“…Since phase separation conditions can affect the quality of the solution NMR spectra, we used substoichiometric ratios of pHP1α to mononucleosomes, which resulted in clear samples without droplets (Figure S5) and yielded well resolved assignable spectra (Figure b). We also note that we performed all NMR structural studies (both solution and solid state) under low salt conditions to compare to previous work and to take advantage of published assignments. …”
Section: Resultsmentioning
confidence: 99%
“…As noted above, high-resolution structural techniques, such as X-ray crystallography or cryo-EM, are generally unable to localize the disordered histone tail domains in nucleosomes. Instead, this problem can be uniquely addressed by multidimensional NMR spectroscopy , in particular, by measurements of residue-specific proton paramagnetic relaxation enhancements (PREs), which report on distances between individual backbone amides and covalent paramagnetic tags attached at specific protein sites and are significant over distances up to ∼20–30 Å. For structured biomolecules in solution, the PRE-based restraints can be used to build or refine structural models, and indeed, studies along these lines have been reported for nucleosome particles and their complexes with CAPs. This approach relies on the well-known Solomon–Bloembergen equation which represents PRE rates as a product of distance- and dynamics-dependent terms, where the latter can be determined from heteronuclear relaxation measurements and the former can be converted into structural restraints.…”
Section: Introductionmentioning
confidence: 99%